DOI: 10.33915/etd.7153
|View full text |Cite
|
Sign up to set email alerts
|

Examination and Characterization of Brook Trout Ecology Before and After a Broad Scale Disturbance Event in Headwater Streams of West Virginia, USA

Abstract: The Appalachian Mountains have experienced comprehensive human disturbance since the colonial period. Activities such as mining, logging, and development for agriculture and residential lands have changed the landscape from the old growth state of centuries past. These disturbances have also led to changes in the forests and their drainage systems over time. Native species like the Brook Trout Salvelinus fontinalis have experienced declines in both size and abundance due to changes in their headwater stream ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…In our study streams, Brook Trout populations have been observed to experience >60% reductions in abundance due to environmental factors such as drought disturbance (Hakala and Hartman 2004). Some populations within our study systems have been observed to respond to disturbances differently than what is observed in the majority of the streams due primarily to demographic and habitat factors (Andrew 2018). Since Brook Trout populations, including our study populations, fluctuate naturally, the N e of our populations may be largely driven by long‐term stability and gene flow rather than short‐term stability.…”
Section: Discussionmentioning
confidence: 98%
“…In our study streams, Brook Trout populations have been observed to experience >60% reductions in abundance due to environmental factors such as drought disturbance (Hakala and Hartman 2004). Some populations within our study systems have been observed to respond to disturbances differently than what is observed in the majority of the streams due primarily to demographic and habitat factors (Andrew 2018). Since Brook Trout populations, including our study populations, fluctuate naturally, the N e of our populations may be largely driven by long‐term stability and gene flow rather than short‐term stability.…”
Section: Discussionmentioning
confidence: 98%